The effects of harmonic components on transformer losses of sinusoidal source supplying non-linear loads - Ismail, Daut; Syafruddin, Hasan; Rosnazri, Ali; Samila, Mat Zali; Haziah, Abd Hamid (Science Publications, 2008)
Link to publisher's homepage at http://scipub.org/scipub/index.php